Intertemporal Cournot and Walras Equilibrium: An Illustration - Tito Cordella; Manjira Datta (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
In a simple dynamic general equilibrium model, we introduce the concept of an intertemporal Cournot equilibrium. We show that if the number of strategic agents increases without limit, the intertemporal Cournot equilibrium converges to the intertemporal Walras equilibrium only when the tune horizon for the agent is finite. If the time horizon is infinite, each strategic agent is able to exert nonnegligible market power, no matter how large their number is.
Keywords: 330